"Listen to me, learn from me": a priority setting partnership for shaping interdisciplinary pain training to strengthen chronic pain care. Issue 11 (6th November 2022) - Slater, Helen; Jordan, Joanne E.; O'Sullivan, Peter B.; Schütze, Robert; Goucke, Roger; Chua, Jason; Browne, Allyson; Horgan, Ben; De Morgan, Simone; Briggs, Andrew M.
Abstract : Supplemental Digital Content is Available in the Text. This empirically derived framework strongly repositions shaping of health workforce training through a genuine partnership lens, strengthening training efforts to support high-quality, person-centred, chronic pain care. Abstract: What are the care-seeking priorities of people living with chronic pain and carers and how can these shape interdisciplinary workforce training to improve high-value pain care? Phase 1: Australian people living with chronic pain (n = 206; 90% female) and carers (n = 10; 40% female) described their pain care priorities (eDelphi, round 1). A coding framework was inductively derived from 842 pain care priorities (9 categories, 52 priorities), including validation; communication; multidisciplinary approaches; holistic care; partnerships; practitioner knowledge; self-management; medicines; and diagnosis. Phase 2: In eDelphi round 2, panellists (n = 170; valid responses) rated the importance (1 = less important; 9 = more important) of the represented framework. In parallel, cross-discipline health professionals (n = 267; 75% female) rated the importance of these same priorities. Applying the RAND-UCLA method (panel medians: 1-3: "not important, " 4-6: "equivocal, " or 7-9: "important"), "important" items were retained where the panel median score was >7 with panel agreement ≥70%, with 44 items (84.6%) retained. Specific workforce training targets included the following: empathic validation; effective, respectful, safe communication; and ensuring genuine partnerships in coplanning personalised care. Panellists and health professionals agreed or strongly agreed (95.7% and 95.2%, respectively) that this framework meaningfully reflected the importance in care seeking for pain. More than 74% of health professionals were fairly or extremely confident in their ability to support care priorities for 6 of 9 categories (66.7%). Phase 3: An interdisciplinary panel (n = 5) mapped an existing foundation-level workforce training program against the framework, identifying gaps and training targets. Recommendations were determined for framework adoption to genuinely shape, from a partnership perspective, Australian interdisciplinary pain training.